Are we there yet? The role of continuous assessment in musical theatre training. Issue 2 (1st June 2014) - Harrison, Scott; Sabey, Paul; O'Bryan, Jessica
This article seeks to interrogate aspects of assessment practices in musical theatre. Practices in the training of musical theatre students are rarely a source for reflection, and this project sought to unveil some of the processes of learning, teaching and assessment in a new musical theatre degree. The larger project on which this article is based sought to develop and evaluate assessment protocols that assisted in facilitating practices with a stronger alignment with the professional realities of musical theatre. The data for this research consists of perceptions of students and their lecturers in relation to the implementation of a continuous assessment regime in a musical theatre degree in Australia. The assessment process is designed to provide students with regular commentary about their progress. In addition to end-of-semester exams, weekly marks are awarded for approximately twenty sub-activities within the broad areas of acting, dance, performance project, singing and speech. In addition, this means of assessment is located within a degree structure that employs a sliding scale across three years: students are assessed through formative assessment in the early years, and summative in the later years of the degree. Through individual interviews with staff and students, the efficacy of this assessment process was documented. Staff members who worked with students in the programme were interviewed to ascertain the strengths and weaknesses of such an approach. Students were interviewed to determine whether they believed it assisted them in both their learning and in achieving goals during and beyond the degree. An action research cycle was initiated and the findings demonstrate a relative degree of agreement between expectations of participants in the course and the proposed outcomes at the end of the degree. These findings, combined with artefacts from the programme and previously reported student perceptions, are presented as a model that may provide the potential for replication in other training programmes that seek to prepare students for the realities of a career in the creative and performing arts.